Picogram detection of metal ions by melanin-sensitized piezoelectric sensor - Huang, G. Steven; Wang, Meng-Te; Su, Chia-Wei; Chen, Yu-Shiun; Hong, Meng-Yen (My University, 2007)
A heavy metal ion sensor was constructed by cross-linking melanin onto the gold electrode of quartz crystal microbalance (QCM). A mercury ion sensitivity of 518 +/- 37 Hz/ppm was observed, a substantial increase in sensitivity compared to previous reports of 10-50 Hz/ppm with the limit of detection at 5 ppb. Detection of other metal ions including Sn2+, Ge4+, Li+, Zn2+, Cu2+, Bi3+, Co2+, Al3+, Ni2+, Ag+, and Fe3+ were also performed. Unexpectedly, binding of Mn7+, Ph2+, Cd2+, and Cr3+ increased resonant frequencies. The surface profile of melanin thin film upon binding to metal ions was investigated by atomic force microscopy (AFM). Structural change of melanin upon binding to metal ions was characterized by circular dichroism and by infrared spectroscopy. The current study provides the first example of melanin-coated piezoelectric sensor showing high sensitivity and selectivity to metal ions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: quartz crystal microbalance; melanin; heavy metal; conformational change; circular dichroism; infrared spectroscopy